The Epistemology of Hadith in Sayyid Sabiq's Fiqh al-Sunnah (Between the Authority of Isnad and the Facilitation of Modern Islamic Law) - Rahmad Ridwan (UIN Sumatera Utara Medan, 2026)
This study discusses the epistemology of Sayyid Sabiq's hadiths in Fiqh al-Sunnah, which attempts to reconcile the authority of hadiths with the need for the modernization of Islamic law. The study is motivated by criticism of Sayyid Sabiq's hadith methodology, which is considered more practical and moderate but less rigorous in terms of sanad and hadith authentication. The study aims to analyze the epistemological characteristics of Sayyid Sabiq's hadiths, the methods of using hadiths in Fiqh al-Sunnah, and their relevance to contemporary Islamic studies. This study is a library research study with an epistemological and historical approach. Data obtained from Sayyid Sabiq's primary works and relevant contemporary hadith and fiqh literature. The results of the study show that the epistemology of the hadith of Sayyid Sabiq is practical, moderate, non-school, and contextual with an orientation towards the principle of taysīr and the welfare of the community. Despite criticism regarding the sanad, Sayyid Sabiq's ideas have made a significant contribution to the modernization of fiqh and the promotion of religious moderation in contemporary Islamic studies.